Laparoscopic Versus Open Inguinal Hernia Repair for Strangulated Inguinal Hernia: A Systematic Review and Meta-Analysis - Coco, Danilo (2025)
Introduction: Strangulated inguinal hernia is a surgical emergency requiring prompt intervention. The choice between laparoscopic and open repair remains controversial, with limited evidence comparing outcomes in the context of strangulation. This study aims to compare the efficacy, safety, and postoperative outcomes of laparoscopic versus open repair for strangulated inguinal hernia. Methods: A systematic review and meta-analysis were conducted following PRISMA guidelines. Databases including PubMed, Embase, and Cochrane Library were searched for studies comparing laparoscopic and open repair for strangulated inguinal hernia. Primary outcomes included operative time, postoperative complications, length of hospital stay, and recurrence rates. Secondary outcomes included mortality and conversion rates. Statistical analysis was performed using RevMan 5.4, with Egger’s test used to assess publication bias. Results: Ten studies involving 1250 patients were included. Laparoscopic repair was associated with shorter hospital stays (mean difference: -1.2 days, 95% CI: -1.8 to -0.6, p < 0.001) and lower rates of wound infections (OR: 0.45, 95% CI: 0.28–0.72, p = 0.001). However, operative time was longer in the laparoscopic group (mean difference: 15.3 minutes, 95% CI: 8.2–22.4, p < 0.001). No significant differences were observed in recurrence rates, mortality, or bowel resection rates. Egger’s test indicated no significant publication bias (p = 0.12). Conclusion: Laparoscopic repair for strangulated inguinal hernia is associated with shorter hospital stays and fewer wound infections but requires longer operative times compared to open repair. Both techniques are comparable in terms of recurrence and mortality rates.